Bioactive Compounds Biosynthesis, Characterization and Applications - Queiroz Zepka, Leila; Casagrande do Nascimento, Tatiele; Jacob-Lopes, Eduardo (IntechOpen, 2021)
Bioactive Compounds - Biosynthesis, Characterization, and Applications is an authoritative compilation of chapters on bioactive compounds with proven activities. It provides valuable information about biosynthesized active compounds that can be used for the further development of products in various industries. Chapters cover such topics as biosynthesis, characterization, separation, and purification, and applications of bioactive molecules. It describes and discusses bioresources of animal, vegetal, and microbial origin as potential sources of flavonoids, polysaccharides, sterols, polyphenols, amino acids, and others. This book provides insight into future developments in the field and, as such, is an essential resource for academicians, industrial researchers, and practitioners in biomolecules with biological activity. Key features: • Describes several classes of bioactive compounds and their associated activities • Highlights potential contributions of bioactive compounds as alternatives in the prevention and/or treatment of diseases • Contains information relevant to the development and use of new products